Clinical role of cardioprotective and vasculoprotective effects of АСЕ inhibitors in myocardial infarction: zofenopril - G. K. Кiyakbaev (Кардиоваскулярная терапия и профилактика)
ACE inhibitors, with their proven beneficial effect on survival, are widely used for treating patients after myocardial infarction (MI). After MI, these agents prevent disadaptive heart and vessel remodelling. The magnitude of ACE inhibitors' cardioprotective and vasculoprotective effects depends on their impact on tissue renin-angiotensin-aldosterone system. As a part of a wide-scale SMILE project, it has been demonstrated that zofenopril, due to its high antioxidant activity and myocardial and vascular tissue penetrant ability, is effective and safe in patients with anterior MI, who have stable hemodynamics and do not receive thrombolytic therapy, regardless of patients' age, myocardial damage size, presence or absence of arterial hypertension and/or heart failure. Clinical evidence had been obtained on antihypertensive-independent anti-ischemic effect of zofenopril, which is known to be one of key cardioprotection mechanisms.